2018
DOI: 10.1177/2515841418817486
|View full text |Cite
|
Sign up to set email alerts
|

Delleman–Oorthuys syndrome (oculocerebrocutaneous syndrome) in a Nigerian child: a case report

Abstract: Background:Delleman–Oorthuys syndrome, also known as oculocerebrocutaneous syndrome, is a rare congenital anomaly with ocular, cerebral and cutaneous manifestations. So far, only 40 cases have been described.Clinical case:A 3-year-old female Nigerian child with no identifiable left eyeball, multiple left-sided facial skin defects and delayed developmental milestones but otherwise uneventful medical and family history was evaluated at the Ophthalmology and Paediatric Neurosurgery in Ibadan, Nigeria. Besides the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…The brain, cutaneous and orbital malformations seen in the index case are consistent with the triad of Oculocerebrocutaneous syndrome [2,[4][5][6][7][8]. With this classical triad of orbital cyst, cerebral and cutaneous malformations characteristics of OCCS on the side as seen in this patient, is common in males and occurs sporadically with no family history and in product of non-consanguineous couple in virtually all documented cases as in the index patient.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The brain, cutaneous and orbital malformations seen in the index case are consistent with the triad of Oculocerebrocutaneous syndrome [2,[4][5][6][7][8]. With this classical triad of orbital cyst, cerebral and cutaneous malformations characteristics of OCCS on the side as seen in this patient, is common in males and occurs sporadically with no family history and in product of non-consanguineous couple in virtually all documented cases as in the index patient.…”
Section: Discussionsupporting
confidence: 74%
“…This group of congenital abnormalities, has been named after the two authors that first described it (as Delleman-Oorthuys syndrome). Since the entity was described, several sporadic manifestations of the syndrome have been reported worldwide including reports from Nigeria [3,4]. The syndrome appears to have a male preponderance with an approximate male to female ratio of 2:1 but no known racial predilection [5].…”
Section: Introductionmentioning
confidence: 99%
“…e current case differs clinically from the previous cases regarding the morphology of the eye anomaly. Our case had rudimentary eye, which had been described in few cases [4].…”
Section: Discussionsupporting
confidence: 56%
“…Mishra and Luthra 4 did a review mentioning only 28 reported cases in the literature. In 2018, Badejo, Fasina, Balogun, et al 1 reported a case of Delleman Oorthuys in a Nigerian girl with typical findings. This was the last case reported in the literature.…”
Section: Discussionmentioning
confidence: 99%